La population de la Côte-Nord - Bussières, Paul (Cahiers de géographie du Québec, 1963)
The history of the settlement of the North Shore region of the Gulf St. Lawrence can be divided into five stages : the periodical visits of Basque and Breton fishermen from the XIV th to the XVII th century ; the repeated concessions from 1653 to about 1820 of coast sectors to companies, such as the Hudson Bay Co., and merchants of Québec who hold exclusive rights of occupation and exploitation ; the foundation of most of the existing agglomerations between 1836 and 1865 when settlers gather around sawmills between Tadoussac and Baie-Trinité and fishermen from the south shore of the Gulf, the Magdalen Islands, Newfoundland and the Channel Islands, sometimes after a long association with the exploitation of the coastal fisheries, establish some 20 hamlets and villages between Sept-lies and Blanc-Sablon ; the consolidation of the population, parallel to the growth of the pulp and paper industry up to the advent of the second world war ; the mass immigration brought about by the mining developments in the 1950's. Various conditions have influenced the distribution of the population and given rise to different types of settlement. These conditions have been : the hold of the wood and pulp companies on the land and the labour force, the absence of industrial diversification in any one sector of the region or, in other words, the over-specialization of the economic activities, the proper requirements of those activities, the particular conditions of the land tenure and of the lot structure and, to a lesser extent, the social background of the immigrants.The settlement outlook is thus as follows. From Tadoussac to Natashquan, the habitat is differenciated : the largest communities have grown at the points of transhipment where man and merchandise journey to and fro, that is near deep sheltered bays ; the villages depending on the export of pulpwood are all sited at the mouth of the rivers and show small but dense concentrations of population ; when agriculture dominates, the « rang » System of rural settlement is prevalent ; below Sept-lies, the population concerned with fishing bas settled in small nuclei at short distance from its fisheries. From Kegashka to Blanc-Sablon, the inhabitants are individualistic, dwell on Crown Lands — often as squatters — and keep jealously to their self-appropriated fishing spots, whence their dispersion. In the backcountry, the mining towns of Schefferville, Wabush, Labrador and Gagnon bear witness of the conceptions that presided to their elaboration.